2013
DOI: 10.1093/rheumatology/ket416
|View full text |Cite
|
Sign up to set email alerts
|

It's like a juggling act: rheumatoid arthritis patient perspectives on daily life and flare while on current treatment regimes

Abstract: Objective. The objective of this study was to explore patients’ experiences of RA daily life while on modern treatments.Methods. The methods of this study comprised semi-structured interviews with 15 RA patients, analysed using inductive thematic analysis.Results. Four themes suggest patients experience life with RA along a continuum from RA in the background to the foreground of their lives, underpinned by constant actions to maintain balance. Living with RA in the background shows patients experience continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 20 publications
(22 reference statements)
8
110
0
3
Order By: Relevance
“…Furthermore, stiffness was not always limited to specific joints, but could vary in location. Exacerbating factors included weather and immobility, and alleviating factors and self-management strategies were described, also consistent with earlier work for multiple RA flare symptoms (2, 15, 16). Of note, in both studies participants described stiffness most often in terms of its impact on day-to-day life activities including getting dressed, driving, cooking, attending (or not) a social event.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, stiffness was not always limited to specific joints, but could vary in location. Exacerbating factors included weather and immobility, and alleviating factors and self-management strategies were described, also consistent with earlier work for multiple RA flare symptoms (2, 15, 16). Of note, in both studies participants described stiffness most often in terms of its impact on day-to-day life activities including getting dressed, driving, cooking, attending (or not) a social event.…”
Section: Resultssupporting
confidence: 81%
“…Even if RA is put back to the background of patient's lives by means of disease-modifying agents, most patients still experience continuous, daily symptoms. [4] RA has a profound impact on participation, from daily life activities, to, for example, a person's working life. [5][6][7] Despite a slight decrease in work disability (permanent exclusion from work) rates over the past decade, permanent work disability still occurs frequently.…”
Section: Introductionmentioning
confidence: 99%
“…RA patients also delay seeking help in order to maintain a feeling of self-management over RA while using microand crisis management techniques. [3] In studies, it has been found that nurses hope for continuous and regular education concerning patient education, in order to develop themselves as professionals. [9] Practice nurses have also expressed their interest in more training in the provision of counselling.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) widely affects patients' everyday lives [1][2][3] and has physical, psychological and social impacts. [4] In Finland, newly diagnosed RA patients have their follow-up controls in hospital, but otherwise care takes place in local health centres.…”
Section: Introductionmentioning
confidence: 99%